United States : Publication of Financial Sector Assessment Program Documentation; Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2010)
This paper presents Detailed Assessment of the United States's observance of Basel Core Principles for Effective Banking Supervision. The U.S. financial system is large and highly diversified. At the end-2007, total U.S. financial assets amounted to almost four and a half times the size of GDP. Of this, however, less than a one-fourth quarter of total financial assets were accounted for by traditional depository institutions. The crisis has radically changed the shape of the U.S. financial system in a short timeframe.